The probable progression of Epstein-Barr virus (EBV) to chronic active EBV/reactivation weakens the immune response and stimulates Cryptococcus neoformans infection, which invariably proves fatal: a case report and review of the literature - Mishra, Gargee; Sarnaik, Gaurav; Samanta, Joydeep; Keche, Archana; Negi, Sanjay Singh (Frontiers in Virology, 2025)
We have reported here the fatal outcome of Epstein-Barr virus (EBV) infection in a 58-year-old male who had probably developed reactivation/chronic active EBV (CAEBV) which gave rise to various neurological deficits, pancytopenia, and a lower CD4 count in the patient. The decreased immune response helped Cryptococcus neoformans (C. neoformans) to manifest a disseminated infection. Although he was exclusively provided with antifungal treatment and the patient appeared to be successfully treated for cryptococcal infection, no coverage of EBV appeared detrimental as the patient died the very next day. This report highlights the need for clinical suspicion of EBV in unexplained cases of neurological manifestation, the hematological disorder of pancytopenia, a lower CD4 count, and multiorgan involvement such as pleural effusion, coarse liver echotexture, and splenomegaly.